Konsep Pendidikan Akhlak Menurut Sa’id Hawwa - Awaliyah, Tuti; Nurzaman, Nurzaman (Jurnal Penelitian Pendidikan Islam, 2018)
This study attempts to explain the concept of moral education according to Sa'id Hawwa. The results showed that (1) moral education according to Sa'id Hawwa is to form the child's personality in an Islamic way so that they have solid moral foundation and Islamic knowledge. The moral basis according to Sa'id Hawwa is loyalty only to Allah, the Messenger of Allah, and the believers; the love of a servant to God; being gentle towards the believers; being stern against the unbelievers; and jihad in the way of Allah